Avaliação da potencialidade de utilização de um solo da cidade de Pau dos Ferros para a fabricação de geotintas - Saldanha, Nayara Mara de Oliveira (Universidade Federal Rural do Semi-Árido, 2019)
Paints have assumed great importance in the construction sector, being essential when it comes to finishing and aesthetics, but what is little known is that this material has Volatile Organic Compounds (VOCs) that are harmful to health. In 1987, the World Health Organization noted that there is a reaction between the symptoms of allergic and respiratory problems that arise in building users and VOCs, after which the number of public health-related research in buildings has progressively increased. In this context, paints that present natural soil as a raw material become an interesting option, since it is a natural paint that does not contain such substances and its production is simple and easily accessible to all. In this sense, the objective of this work was to evaluate the potential of a Pau dos Ferros soil for the production of a geotint and to evaluate parameters such as workability, yield, durability, cost benefit, among others. As a methodology, we opted for a qualitative research, relying on data collection techniques, also quantitative. Regarding the procedures, the research initially consisted of a literature review on the subject, then divided into three experimental steps: soil characterization, geotint production with two different granulometries and application of the product on two different substrates. . Through the analysis performed in this work, it was found that the geotint with smaller specific surface (L geotint) had a better performance in relation to all the analyzed aspects except the durability, which showed the same result for both types of geotint.
Keywords: Tintas naturais; COV’s; Caracterização do solo; Natural paints; VOCs; Soil characterization; ENGENHARIAS::ENGENHARIA CIVIL